2021
DOI: 10.3102/0013189x211065752
|View full text |Cite
|
Sign up to set email alerts
|

Challenging Scripted Curricula With Adaptive Teaching

Abstract: Although adaptive teaching is considered a cornerstone of effective instruction, there remains a lack of focus on teacher adaptability in policy, professional practice, and teacher education in the United States. High-profile educational reform efforts have pressured districts and states across the nation to rely on prescriptive curricula that fail to meet the linguistic, cultural, and instructional needs of the nation’s diverse student population. In this article, we describe the development of the Adaptive T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
1
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 68 publications
0
15
1
2
Order By: Relevance
“…These discrete elements also offer insight into both the policy and school-level conditions that are necessary for the development of decisional capital. As a baseline condition, agency is essential because removing teachers' ability to make decisions and act autonomously within their context hinders their development of judgment (Vaughn et al, 2022). Considering the three elements proposed in this study also highlights that all three are important to the development of decisional capital; one can easily imagine a teacher who has good reflective practices, but without the confidence to act on those reflections they are not useful (Lee, 2021).…”
Section: Discussionmentioning
confidence: 82%
See 2 more Smart Citations
“…These discrete elements also offer insight into both the policy and school-level conditions that are necessary for the development of decisional capital. As a baseline condition, agency is essential because removing teachers' ability to make decisions and act autonomously within their context hinders their development of judgment (Vaughn et al, 2022). Considering the three elements proposed in this study also highlights that all three are important to the development of decisional capital; one can easily imagine a teacher who has good reflective practices, but without the confidence to act on those reflections they are not useful (Lee, 2021).…”
Section: Discussionmentioning
confidence: 82%
“…Agency: room to make decisions The development of decisional capital is, to some extent, a policy choice: teachers must have room to employ their professional judgment in order to exercise decisional capital at all (Kitsing et al, 2016;Vaughn et al, 2022). For example, scripted curricula may lead to an erosion of decisional capital (Vaughn et al, 2022) while transferring increasing authority for decision-making to schools and teachers allows it to flourish (Kitsing et al, 2016). Without the latitude for decision-making and judgment, decisional capital (and thus, professional capital) is simply impossible to leverage (Pino-Yancovic et al, 2020).…”
Section: Conceptualizing Decisional Capitalmentioning
confidence: 99%
See 1 more Smart Citation
“…Yet, despite this perspective, representations of Black, Brown, Latinx, and other minoritized individuals in children’s literature remains critical (Bishop, 1990 ; Derman-Sparks, 1989 ; Mendoza and Reese, 2001 ), and high-interest and culturally responsive YA texts are not widely embedded into high school Language Arts programs (Timberlake et al, 2017 ). Plausible reasons for this include: neoliberal educational reforms that promote a standardized approach to instruction (Vaughn et al, 2022 ), persistent underfunding of public schools (Timberlake, 2017 ), and a lack of representation of historically underrepresented individuals across widely adopted curricular programs (Newvine and Fleming, 2021 ; Vaughn et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…Deunk et al, 2018;Prast et al, 2018), "adaptive teaching" (e.g. Hardy et al, 2019;Vaughn et al, 2021), "instructional adaptations" (e.g. Parsons et al, 2018) are among the most common found in the literature.…”
Section: What Is Individualized Instruction?mentioning
confidence: 99%